Spherical-shaped Y2O3:Eu3+ nanoparticles with intense photoluminescence emission - Mayrinck, Caroline de; Schiavon, Marco Antonio; Nascimento, Clebio Soares; Guimaraes, Luciana; Davolos, Marian Rosaly [UNESP]; Goes, Marcio de Sousa; Goncalves, Rogeria Rocha; Pires, Ana Maria [UNESP]; Lima Ribeiro, Sidney Jose [UNESP]; Ferrari, Jefferson Luis (Elsevier B.V., 2015)
Herein we report on the crystallized nanoparticles based on Eu3+-doped Y2O3 with 5 mol% using citric acid as precursor. The heating temperatures were evaluated in order to obtain the best crystallized nanoparticles with size around 12 nm and with highest red intense photoluminescence emission. Nanocrystallite size was calculated by Scherrer's equation based on diffractogram of the material heated at 750 degrees C for 4 h, obtaining size around 8 nm. The low photoluminescence intense emissions were attributed to the presence of quenchers remaining from precursors used in the synthesis. In general the photoluminescence properties were evaluated based on emission and excitation spectra profile. Rietveld refinement was performed based on the diffractogram of the material annealed at 750 degrees C for 4 h, and the visualization of the cubic structure was obtained. The centered cubic crystalline structure of Y2O3 was obtained and the photoluminescence properties of Eu3+ ion in Y2O3 host lattice was verified as being dependent on the temperature of heating and C-2 and S-6 site of symmetry present in the cubic structure. CIE chromaticity diagram was obtained with x and y being 0.682 and 0.316, respectively, for material with the highest relative photoluminescence intensity. (C) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Yttrium oxide; Nanoparticles; Photoluminescence; Rare earths